Workplace Exposure to Nanoparticles From Gas Metal Arc Welding Process - Zhang, M.; Jian, Le; Bin, P.; Xing, M.; Lou, J.; Cong, L.; Zou, H. (Springer Netherlands, 2013)
Workplace exposure to nanoparticles from gas metal arc welding (GMAW) process in an automobile manufacturing factory was investigated using a combination of multiple metrics and a comparison with background particles. The number concentration (NC), lung-deposited surface area concentration (SAC), estimated SAC and mass concentration (MC) of nanoparticles produced from the GMAW process were significantly higher than those of background particles before welding (P < 0.01). A bimodal size distribution by mass for welding particles with two peak values (i.e., 10,000-18,000 and 560-320 nm) and a unimodal size distribution by number with 190.7-nm mode size or 154.9-nm geometric size were observed. Nanoparticles by number comprised 60.7% of particles, whereas nanoparticles by mass only accounted for 18.2% of the total particles. The morphology of welding particles was dominated by the formation of chain-like agglomerates of primary particles. The metal composition of these welding particles consisted primarily of Fe, Mn, and Zn. The size distribution, morphology, and elemental compositions of welding particles were significantly different from background particles. Working activities, sampling distances from the source, air velocity, engineering control measures, and background particles in working places had significant influences on concentrations of airborne nanoparticle. In addition, SAC showed a high correlation with NC and a relatively low correlation with MC. These findings indicate that the GMAW process is able to generate significant levels of nanoparticles. It is recommended that a combination of multiple metrics is measured as part of a well-designed sampling strategy for airborne nanoparticles. Key exposure factors, such as particle agglomeration/aggregation, background particles, working activities, temporal and spatial distributions of the particles, air velocity, engineering control measures, should be investigated when measuring workplace exposure to nanoparticles.